The Implementation of Directed Reading Thinking Activity (DRTA) Strategy in Teaching Reading Comprehension using Procedure Text at Vocational High School Students - Firahmahira, Puspita; Al-Baekani, Abdul Kodir; Utami, Praditya Putri (Peneliti.net, 2024)
This study aims to find out the implementation of Directed Reading Thinking Activity (DRTA) strategy in teaching reading comprehension with the type of text being used is Procedure Text with the students’ reaction and response as well. This study used descriptive case study, which is a qualitative research. The participants of this study were 35 vocational high school students in 10th grade with culinary art major. Data collection techniques that researchers will use are observation checklist & interviews. This study will use thematic analysis from Braun & Clarke (2006) to analyze the data. The results of this study were Directed Reading Thinking Activity (DRTA) strategy has been well-implemented in teaching reading comprehension with Procedure Text and the student responses at the time of implementation varied.